Estimating the Willingness to Pay for Improving Road Safety in the Turkish Republic of Northern Cyprus - Niroomand, Naghmeh (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
The incidence of fatalities over the period 2010 to 2014 from automobile accidents in North Cyprus is 2.75 times greater than the average for the EU. With the prospect of North Cyprus entering the EU, many investments will need to be undertaken to improve road safety in order to reach EU benchmarks. The objective of this study is to provide local estimates of the value of a statistical life and injury along with the value of time savings. These are among the parameter values needed for the evaluation of the change in the expected incidence of automotive accidents and time savings brought about by such projects. In this study we conducted a stated choice experiment to identify the preferences and tradeoffs of automobile drivers in North Cyprus for improved travel times, travel costs, and safety. The choice of route was examined using mixed logit models to obtain the marginal utilities associated with each attribute of the routes that consumers choose. These estimates were used to assess the individuals’ willingness to pay (WTP) to avoid fatalities and injuries and to save travel time. We then used the results to obtain community-wide estimates of the value of a statistical life (VSL) saved, the value of injury (VI) prevented, and the value per hour of travel time saved. The estimates for the VSL range from €315,293 to €1,117,856 and the estimates of VI from € 5,603 to € 28,186. These values are consistent, after adjusting for differences in incomes, with the median results of similar studies done for EU countries.

ÖZ: Kuzey Kıbrıs’ta yaşanılan otomobil kazalarından kaynaklı ölüm vakaları 2010 ve 2014 yılları arasında değerlendirildiğinde Avrupa Birliği (AB) ortalamasının 2.75 katı büyüklüğünde gerçekleşmiştir. Kuzey Kıbrıs’ın Avrupa Birliği’ne girme yolunda, AB kriterlerine ulaşıp yol güvenliğini artırması için bir çok yatırım yapması gerekmektedir. Bu çalışmanın amacı, zaman tasarrufu değeriyle birlikte istatistiksel yaşam ve yaralanma değerlerinin yerel tahminlerinin temin edilmesidir. Bunlar, bu tür projelerin getirdiği, beklenen otomotiv kaza vakaları ve zaman tasarrufu değişiminin değerlendirilmesi için gerekli parametre değerleri arasında olmasıdır. Bu çalısmada, belirlenmiş tercih yapma deneyi ile, Kuzey Kıbrıs’taki araba sürücülerinin geliştirilmiş seyehat süreleri, maliyetleri ve güvenliği arasındaki denge ile yapmış oldukları tercihler ele alınmıştır. Yöntem seçimi , tüketicilerin tercih yollarının her öznitelik ile ilişkili marjinal yarar elde etmek için karışık logit modelleri kullanılarak incelenmiştir. Bu tahminler ölümleri ve yaralanmaları önlemek ve seyahat süresinden kazanmak için bireylerin göstermiş olduğu ödeme eğilimlerini değerlendirmek için kullanılmıştır. Daha sonra, toplum genelinde sonuçlar elde etmek için istatistiki hayat değerlerini (VSL), yaralanma değerlerini (VI) ve seyahat süreleri değerleri gözlemlenmiştir. Sonuçlara bakıldığında VSL değerleri €315,293 ile €1,117,856 aralığında iken VI değerleri ise € 5,603 ile € 28,186 aralığındadır. Sonuçlara bakıldığında bu değerler, gelir farklılıklarına göre, AB için yapılan benzer çalışmaların sonuçları ile tutarlılık göstermektedir.
Doctor of Philosophy in Economics. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2016. Supervisor: Prof. Dr. Glenn P. Jenkins.
Keywords: Roads--Design and construction--Safety measures--Cyprus, North; Traffic safety--Road Safety--European Union Countries; Investments--Roads--Cyprus, North; Willingness to pay; choice experiment; value of risk reduction; road safety; car drivers; Economics